The Influence Of Internal Control And Human Resource Competence On Financial Decision-Making: The Mediating Role Of Accounting Information System Implementation In Royal Group - Rhevi Aditya Salinda; Achmad Fadjar (Paradoks : Jurnal Ilmu Ekonomi, 2026)
In a volatile global economy, the precision of financial decisions determines the survival of manufacturing entities. This research aims to provide a comprehensive analysis of how Internal Control and Human Resource (HR) Competence influence Financial Decision-Making at Royal Group, using the implementation of an Accounting Information System (AIS) as an intervening variable. The study employs a quantitative methodology with path analysis, utilizing data from 240 respondents across five subsidiaries. The findings reveal that while Internal Control and HR Competence are foundational, their impact on strategic decision-making is significantly amplified when channeled through a robust AIS (JD Edwards Oracle). This research contributes to the literature by highlighting the necessity of technological integration in human-centric organizational frameworks.